Analisa Lapisan Sedimen Bawah Permukaan Pada Pembangunan Jalan Elevated Danau Dendam Tak Sudah Kota Bengkulu Menggunakan Metode HVInv - Setyowati, Yuni; Farid, Muchammad; Ismul Hadi, Arif; Helinnes, Putri; Hardiansyah, Debi; Refrizon, Refrizon; Gumanty, Usman; Raihana, Hana; Rahmat Al-Ansory, Andre; Taufiqurrahman Syah, Muhammad (Jurusan Fisika FMIPA Universitas Andalas, 2024)
Bengkulu City is situated within a subduction zone where the Indo-Australian and Eurasian tectonic plates converge, rendering the area highly susceptible to seismic activity. This study employs the microseismic method to assess seismic vulnerability and the subsurface rock structure at the Dendam Tak Sudah Lake Flyover Construction Site in Bengkulu City, which encompasses a swampy region. The microseismic method used was an inversion of the horizontal to vertical (H/V) spectral ratio (HV-Inv) for determining the dominant frequency (f0), amplification factor (A0), seismic sensitivity index (Kg), and shear wave velocity (Vs). The findings reveal that f0 in the study area range from 2.16 to 7.53 Hz, A0 vary from 0.40 to 3.79, and Kg values span from 0.03 to 6.04. The sedimentary layers exhibit an average thickness of 5-10 meters, with some locations showing significantly thicker sedimentary deposits. Notably, the highest seismic susceptibility is recorded at point T8. The Vs values range from 185.19 to 539.49 m/s, which are inversely proportional to the Kg values and indicate soil classifications varying from soft to medium. The overall seismic risk in the study area is moderate. These results offer key insights into geophysical and geological conditions in Bengkulu City, crucial for earthquake mitigation.